Picture Of Hematological Blood Parameters Characterizing The Development Of Health Disorders In Workers Of Oil Refineries In Central Asia - I.Sh.Sadykov; D.S. Allayorova; O.Bekhbudov (Euro Asian Journal Publishing, 2024)
The socio-economic development of any state depends on labor resources, their quantity and the health status of the able-bodied population. One of the main tasks of modern medicine is to preserve the health of people who are able to work for the benefit of their country. According to the literature, today there is an increase in occupational and production-related diseases, the complication of primary diagnosed pathology, and a high percentage of chronic disorders. Of this population, approximately 78 to 80% of diseases are the result of occupational and environmental factors
Keywords: hematological parameters of blood; erythrocytes; hemoglobin